Discussion and experiments on the limits of chloride, sulphate and shell content in marine fine aggregates for concrete. (20th January 2018) - Liu, Wei; Huang, Ruihua; Fu, Jiyang; Tang, Waiching; Dong, Zhijun; Cui, Hongzhi
Highlights: Limit values of chloride, sulphate and shell contents in the marine aggregates in different countries were discussed. A better understanding on the rationale behind the limit values was provided. An experimental study was carried out to evaluate the rebar corrosion in concrete mixed with DMS. This study can contribute to fill the knowledge gap on DMS application and relative research. Abstract: Concrete is the most consumable building material in the world. Marine aggregates are the natural sand and gravels available in the sea or dredged from seabed. Contents of chloride, sulphate and shell in the marine aggregates can influence the properties of concrete and corresponding performance of the concrete structures. However, the limitations of chloride, sulphate and shell contents are set as different threshold values in different countries and/or regions. Some of them are inconsistent or puzzling for user. This paper presents a comprehensive review on the limit values of these contents used in different countries and provides a better understanding on the rationale behind these limit values thorough analysis on the limits of chloride, sulphate and shell content in marine fine aggregates for concrete. Except discussion, in this paper, an experimental study was carried out to evaluate the corrosion of reinforcing steel in concrete mixed with DMS as well. The experimental results of corrosion potential and corrosion current density showed that the rebar in DMS concrete should be safe from corrosion when the chloride content in DMS is less than 0.18% or the total chloride content in concrete is less than 0.34%. This study can contribute to fill the knowledge gap on concrete applications on dredged marine sand (DMS) and relative research.